1990
DOI: 10.1111/j.1651-2227.1990.tb11460.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Clearance of Asymptomatic Bacteriuria in Infants

Abstract: In an unselected population of 3,581 infants, 14 girls and 36 boys were found to have bacteriuria verified by suprapubic aspiration. Among the bacteriuric infants, one girl and one boy developed symptoms of pyelonephritis close to the time of detection; the others remained asymptomatic. Eleven girls and 34 boys were left untreated. One of these girls and 7 of the boys became abacteriuric after treatment for respiratory tract infections. Ten girls and 26 boys became spontaneously abacteriuric, with a median per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 19 publications
2
27
0
1
Order By: Relevance
“…Wettergren et al 8,9 performed screening bag urine cultures on 3581 asymptomatic infants at 3 separate intervals during the first year of life, beginning at 0.25 to 2 months. Infants with $50 000 CFU/mL from 2 successive bag cultures underwent suprapubic aspiration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wettergren et al 8,9 performed screening bag urine cultures on 3581 asymptomatic infants at 3 separate intervals during the first year of life, beginning at 0.25 to 2 months. Infants with $50 000 CFU/mL from 2 successive bag cultures underwent suprapubic aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 of the 45 untreated infants were diagnosed with pyelonephritis within 2 weeks of detection of the bacteriuria. 9 Follow-up tests for renalconcentrating capacity (a measure of renal function) were done in 47 of 50 children and were normal. 8 In a study by Hoberman et al, 7 of 212 children ,2 years of age with positive urine cultures (.50 000 CFU/mL), 22 patients had ,10 WBC/mm 3 from an enhanced UA (equivalent to ∼2 WBC/ HPF from an automated UA 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All infants had bag urine cultures performed at 2 weeks, 3 months and 10 months of age. Positive cultures were always confirmed with a culture of urine collected by a supra-pubic bladder puncture [14].…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%
“…In the same cohort of children, another 1.2% of the boys and 1.1% of the girls developed an episode of febrile symptomatic UTI. Follow-up studies showed that the ABU lasted between 0.5 and 7.5 months (median of 2 and 1.5 months for the girls and boys, respectively) and had resolved spontaneously without any signs of kidney scarring by the 6-year follow-up [14][15][16]. A subsequent Turkish study which only used clean catch cultures, without confirmation on urine collected by SPA, showed a prevalence of bacteriuria in 4% of newborns and 5.2% of infants [17].…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%